Studi eksplorasi entreprenurial intention berdasarkan Theory of Planned Behavior dan Theory of Entrepreneurial Event pada mahasiswa Institut Informatika dan Bisnis Darmajaya - Stefanus Rumangkit; Sri Rahayu; Yan Aditiya (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2022)
One of the goals of IIB Darmajaya is to become an Entrepreneurial University, which is included in one of the indicators of a world-class university. This research aims to determine the forming factors that can increase students' desire to become entrepreneurs. This study is important because the output of this research is to know the driving factors that exist in students becoming entrepreneurs. The population of this research is students who have taken technopreneur courses totaling 1104 students. The sample used was 92 students. The data analysis method used is the multiple linear regression analysis methods. Based on the results of hypothesis testing, it was found that Self-Efficacy, Subjective Norms, Perceived Desirability, Perceived Feasibility, and Propensity To Act affected Entrepreneurial Intention. This means that to increase Entrepreneurial Intention, students need to pay attention to the constituent variables, namely Self-Efficacy, Subjective Norms, Perceived Desirability, Perceived Feasibility, and Propensity To Act